Policy analysis of the Global Financing Facility in Uganda - Phillip Wanduru; Doris Kwesiga; Mary Kinney; Asha George; Peter Waiswa (Taylor & Francis Group, 2024)
Background In 2015, Uganda joined the Global Financing Facility (GFF), a Global Health Initiative for Reproductive, Maternal, Newborn, Child, and Adolescent Health (RMNCAH). Similar initiatives have been found to be powerful entities influencing national policy and priorities in Uganda, but few independent studies have assessed the GFF. Objective To understand the policy process and contextual factors in Uganda that influenced the content of the GFF policy documents (Investment Case and Project Appraisal). Methods We conducted a qualitative policy analysis. The data collection included a document review of national RMNCAH policy documents and key informant interviews with national stakeholders involved in the development process of GFF policy documents (N = 16). Data were analyzed thematically using the health policy triangle. Results The process of developing the GFF documents unfolded rapidly with a strong country-led approach by the government. Work commenced in late 2015; the Investment Case was published in April 2016 and the Project Appraisal Document was completed and presented two months later. The process was steered by technocrats from government agencies, donor agencies, academics and selected civil society organisations, along with the involvement of political figures. The Ministry of Health was at the center of coordinating the process and navigating the contestations between technical priorities and political motivations. Although civil society organisations took part in the process, there were concerns that some were excluded. Conclusion The learnings from this study provide insights into the translation of globally conceived health initiatives at country level, highlighting enablers and challenges. The study shows the challenges of trying to have a 'country-led' initiative, as such initiatives can still be heavily influenced by 'elites'. Given the diversity of actors with varying interests, achieving representation of key actors, particularly those from underserved groups, can be difficult and may necessitate investing further time and resources in their engagement.